Influence Profitability, Solvability, Liquidity and Credit Risk on Stock Price - Juan Graceo; Eny Purwaningsih (Oikonomia : Journal of Management Economics and Accounting, 2025)
The aim of this research is to empirically review the impact of profitability, solvency, liquidity and credit risk on the share prices of conventional banking entities listed on the IDX in the 2018-2021 period. Independent variables are used, profitability uses Return on Assets, solvency uses Debt to Equity Ratio, liquidity uses Loan to Deposit Ratio, credit risk uses Non-Performing Loans, and the dependent variable is price. Shares use the closing price (31 May t+1) and in 2019 use the closing price (31 July). There are 24 entities with a total of 96 sample data that meet the criteria for research objects in conventional banking companies listed on the IDX during 2018-2021. This research method uses classic assumption tests such as normality, multicollinearity, heteroscedasticity and autocorrelation used in this research. Furthermore, the hypothesis is tested with the F test, t test and the coefficient of determination. The research test uses multiple regression analysis with multiple regression equation models. Based on the test findings, it is known that profitability gave positive results on stock prices. Also, the level of debt and liquidity has a negative impact on stock prices, then credit risk has no impact on stock prices